(3YeOI GdcJGH hYOI Phj GdCdHGH aj UfGYI GdCbdGe hGdMHQ hGdJPgjH hGdCUHGZs - (3GdeYR Hf HGOjS Hf GdefUhQ GdUfgGLj , J (B454 (3g` s ((3CMeO Hf eUWai GdefGSJQj GdeOfj s)
(3ChdgG (B:s
(3hHYO aEfi LeYJ aj gPG GdcJGH GdoeSei YeOI GdcJGH hYOI Phj GdCdHGH eG Zfi ddcGJH s
(3BNQgG (B:s
(3hde CJQc ef BdGJ GdJLdjO TjFkG hbO PcQJg hHGddg GdJhajb s
(3GdfSNI HgG MhGTs
(3HChdg Jedcs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3eUOQ GbJfGA GdCUd (B:s
(3QVG QGeHhQ (B(3763) s
Keywords: (3GdeYGQa GdYGeIs